MEASURE CHARACTERISTICS OF MOTOR TESTS FOR ASSESSING RHYTHMIC STRUCTURE AND EXPLOSIVE STRENGTH WITH KARATE ATHLETES AND NON-ATHLETES AT THE AGE OF 12 - Žarko Kostovski; Georgi Georgiev (Sport Scientific And Practical Aspects, 2025)
The research was conducted on a sample of 200 male entities aged 12. The sample was divided into two subsamples. The first sub-sample consisted of 100 karate-athletes and the second sub-sample consisted of 100 pupils from primary school in Skopje. In order to determine and compare their measure characteristics, the entities were tested by three tests of composite character (performed repeatedly for 4 times each): one for estimating the rhythmic structure, and two tests for the explosive power. The data is calculated by the basic statistic parameters, and the measure characteristics are determined by: Pearson’s coefficient of correlation, Hotelling’s factor analysis, Chronbach’s  coefficient, Spearman-Brown’s coefficient of reliability and mean correlation. The three applied tests show satisfactory measure characteristics, mainly in validity and reliability, with the karate-athletes and the school-boys. Apart from the other relations, it is determined that with the karate-athletes the tests of non-rhythmic hand tapping and standing long jump differ in respect of higher value of the measure characteristics, whereas regarding the test of 20 meter high start running, the data obtained for the two groups is of maximum identity.